The effect of an attention strategy in the learning of the long jump - Josiane Medina-Papst; Cristiane R. C. Candido; Ernani Xavier Filho; Inara Marques (Desafio Singular, 2010)
The purpose of this study was to verify the effect of a strategy of attention in the learning of the long jump. The sample consisted of 55 children, with age ranging from 11 to 12 years. The study's design consisted of a pre-test, post-test 1, post-test 2 and retention evaluation. After post-test 1, the children were divided into the cue group (CG), which received visual information (a fixed target on the wall) and a control group which did not receive the cue (NCG). Anova two-way and Tukey (HSD) post-hoc test were applied (p < .05). The results showed significant improvement in both groups as a result of practice, with no statistically significant effect of the cue in long jump performance. Thus, in spite of performance improvements, we conclude that the use of this learning cue was not specific enough to direct the attention of the learners so as to have significant effects on performance. Another hypothesis is that practice time was not enough for this information to become relevant.